Bioenergetic valorization of Sargassum fluitans in the Mexican Caribbean: The determination of the calorific value and washing mechanism - José A. Sosa Olivier; José R. Laines Canepa; David Guerrero Zarate; Anabel González Díaz; Donato A. Figueiras Jaramillo; Heidi K. Osorio García; Berenice Evia López (AIMS Energy, 2022)
The advent of large volumes of Sargassum sp. on the Mexican Caribbean coast has become an emerging issue for the Mexican population. The most frequent action is harvesting, but a correct treatment or energy recovery strategy is still missing. This work aimed to evaluate the energy potential of Sargassum fluitans, through elemental calculations and direct measurements, considering the effect of its washing. The calorific value determined by the direct method was 9.24 ± 0.28 MJ/kg and 12.64 ± 0.18 MJ/kg for dirty and washed Sargassum, respectively. The washing effect increased the calorific values in Sargassum fluitans by 36.80%. The washing effect increased the calorific values determined by indirect methods, increasing 10.10% and 41.04%, each method, respectively. The content of toxic metals was lower in both materials than that established for non-woody biomass from energy use, concerning the ISO 17225:2014 standard. The unit energy cost of Sargassum fluitans is ＄0.007 and ＄0.011 per MJ for dirty and washed conditions, respectively. Finally, the results of this work indicate that the Sargassum wash provides better characteristics to be considered an alternative fuel option in combustion systems such as thermo-electric plants (based on carbon), sugar mills, and cement kilns with co-processing of solid waste. Attending from a bioenergetic approach, Sargassum's emerging seasonal problem affects the Mexican Caribbean coast.